2018
DOI: 10.1080/2162402x.2018.1432328
|View full text |Cite|
|
Sign up to set email alerts
|

Restricted T cell receptor repertoire in CLL-like monoclonal B cell lymphocytosis and early stage CLL

Abstract: Analysis of the T cell receptor (TR) repertoire of chronic lymphocytic leukemia-like monoclonal B cell lymphocytosis (CLL-like MBL) and early stage CLL is relevant for understanding the dynamic interaction of expanded B cell clones with bystander T cells. Here we profiled the T cell receptor β chain (TRB) repertoire of the CD4 and CD8 T cell fractions from 16 CLL-like MBL and 13 untreated, Binet stage A/Rai stage 0 CLL patients using subcloning analysis followed by Sanger sequencing. The T cell subpopulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Although cytomegalovirus (CMV) infection has shown to induce T-cell expansion and modulate the distribution of differentiation subsets, the exhaustion observed in T cells from CLL patients resulted to be independent from CMV serostatus (82,(93)(94)(95). The progressive skew of the T-cell receptor (TCR) repertoire occurring during disease progression, may suggest a tumor-related antigen-mediated selection (96,97). In line with this observation, an oligoclonal CD8+ effector T-cell population, that expands along with CLL progression and controls disease development, was observed in both CLL patients and mice bearing a CLL-like disease (90).…”
Section: Phenotypic and Functional T-cell Alterationsmentioning
confidence: 99%
“…Although cytomegalovirus (CMV) infection has shown to induce T-cell expansion and modulate the distribution of differentiation subsets, the exhaustion observed in T cells from CLL patients resulted to be independent from CMV serostatus (82,(93)(94)(95). The progressive skew of the T-cell receptor (TCR) repertoire occurring during disease progression, may suggest a tumor-related antigen-mediated selection (96,97). In line with this observation, an oligoclonal CD8+ effector T-cell population, that expands along with CLL progression and controls disease development, was observed in both CLL patients and mice bearing a CLL-like disease (90).…”
Section: Phenotypic and Functional T-cell Alterationsmentioning
confidence: 99%
“…T-cell clonal expansion parallels the numerical increase of clonal B cells. Hence, it has been suggested that select T-cell clones expand in response to tumor-specific antigens [24]. In recent years, sequencing of the TRBV CDR3 region has been used to study the T-cell repertoire, diversity of TCR subfamilies and antigen-specific expansion of T-cell clones.…”
Section: T-cell Receptor Repertoirementioning
confidence: 99%
“…T-cell receptor (TCR) repertoires of CD4 + and CD8 + T cells in CLL show decreased diversity and skewed clonal expansion [32,33]. Expanded T-cell clones in CLL persist over time, and T-cell expansion correlates with tumor load, leading to the hypothesis that expanded T-cell clones contain tumor-specific T-cell populations [32,33].…”
Section: Immunomodulation Of Effector Cells In Cllmentioning
confidence: 99%